2008
DOI: 10.4025/actasciagron.v24i0.2277
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades físicas de um LATOSSOLO VERMELHO Distrófico influenciadas por sistemas de preparo do solo utilizados para implantação da cultura da mandioca

Abstract: RESUMO.A regiã o Noroeste do Estado do Paraná apresenta, na maior parte da sua extensã o, solos de textura mé dia a arenosa que, dependendo do sistema de preparo e manejo do solo e das culturas, podem ser predispostos a elevados ní veis de degradaç ã o fí sica. O objetivo deste trabalho foi avaliar algumas propriedades fí sicas de um LATOSSOLO VERMELHO Distró fico, sob trê s sistemas de preparo do solo, para a implantaç ã o da cultura da mandioca (Euphorbiaceae). O experimento foi instalado em á rea da Fazenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
1
2
0
10
Order By: Relevance
“…For the same soil density values, it is observed that the cone index values increase with the decrement of soil water content, in agreement with Busscher et al (1997), Cunha et al (2002), Tormena et al (2002) and Watanabe et al (2002), except for values under 1.21 g cm -3 , in moisture U4, for the same values, in U3. This fact can be explained because, by removing the disk used on the cylinder to subordinate the soil to compression when the specimens were compacted, it was noticed that the surface was not aggregated enough (loose soil), a fact that was characterized in the last layer.…”
Section: Resultssupporting
confidence: 74%
“…For the same soil density values, it is observed that the cone index values increase with the decrement of soil water content, in agreement with Busscher et al (1997), Cunha et al (2002), Tormena et al (2002) and Watanabe et al (2002), except for values under 1.21 g cm -3 , in moisture U4, for the same values, in U3. This fact can be explained because, by removing the disk used on the cylinder to subordinate the soil to compression when the specimens were compacted, it was noticed that the surface was not aggregated enough (loose soil), a fact that was characterized in the last layer.…”
Section: Resultssupporting
confidence: 74%
“…A avaliação das condições físicas do solo da área experimental realizada por Watanabe et al (2002) e por Cavalieri (2004 nos dois primeiros anos de cultivo, indicou maiores valores de densidade do solo quando o mesmo foi submetido ao PD, seguido do PM e do PC; esses resultados explicam o menor crescimento das plantas nos sistemas que promoveram menor revolvimento do solo. A maior altura de plantas no PM no ano 2 pode ser decorrente da melhor distribuição de chuvas verificada neste período (Figura 1).…”
Section: Resultsunclassified
“…A degradação física do solo em áreas cultivadas com canade-açúcar é devida ao manejo intensivo, com o que o manejo inadequado dos solos e a utilização de máquinas e equipamentos pesados acarretam no incremento da compactação do solo, causando a degradação cumulativa da qualidade física do solo ao longo dos anos de cultivo (Watanabe et al, 2002;Carvalho et al, 2008;Roque et al, 2010).…”
Section: Introductionunclassified